2021
DOI: 10.1186/s12961-020-00673-y
|View full text |Cite
|
Sign up to set email alerts
|

Health provider perspectives on the implementation of the same-day-ART initiation policy in the Gauteng province of South Africa

Abstract: Background In September 2016, South Africa (SA) began implementing the universal-test-and-treat (UTT) policy in hopes of attaining the UNAIDS 90-90-90 targets by 2020. The SA National Department of Health provided a further directive to initiate antiretroviral therapy (ART) on the day of HIV diagnosis in September 2017. We conducted a qualitative study to determine the progress in implementing UTT and examine health providers' perspectives on the implementation of the same-day initiation (SDI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 44 publications
6
30
0
Order By: Relevance
“…In many countries including South Africa, the prevention benefits of ART are not widely emphasised in public health messaging, school-based HIV curricula, nor HIV counselling. 24 Although stable serodiscordant couples in HIV care are increasingly counselled on TasP, this represents a small fraction of young adults at risk. Consistent with the lack of emphasis on TasP in clinical settings, we found no differences in TasP knowledge by recent use of HIV testing nor by gender (despite gender disparities in care-seeking).…”
Section: Behaviourmentioning
confidence: 99%
“…In many countries including South Africa, the prevention benefits of ART are not widely emphasised in public health messaging, school-based HIV curricula, nor HIV counselling. 24 Although stable serodiscordant couples in HIV care are increasingly counselled on TasP, this represents a small fraction of young adults at risk. Consistent with the lack of emphasis on TasP in clinical settings, we found no differences in TasP knowledge by recent use of HIV testing nor by gender (despite gender disparities in care-seeking).…”
Section: Behaviourmentioning
confidence: 99%
“…The literature review was augmented by in-depth interviews with three clinic managers and four lay HIV counsellors of four primary health clinics in Johannesburg between October and December 2017, exploring current approaches to creating demand for uptake of ART and long-term adherence to ART (demand creation for ART) (Onoya et al, 2018). Interviews were audiorecorded, recordings were transcribed verbatim and analysed thematically using NVivo 11 (Onoya et al, 2018). We found that approaches for ART demand creation were inconsistent and counsellor dependent (Figure 1 in supplementary materials) (Onoya et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…SLATE I (Simplified Algorithms for Treatment Eligibility I) [3] and SLATE II [4] were designed as simple, clinical algorithms that require no point-of-care laboratory testing and can be used by existing healthcare personnel to distinguish patients who can start ART that day, even if they have mild symptoms of illness, from those who require additional care prior to initiation. While evidence from the SLATE trials [5,6] and others [7,8] demonstrates improved uptake of ART with SDI compared to standard care, concerns remain whether the benefits of SDI can be translated into improved retention once on treatment, or if instead attrition is simply shifted from before to soon after ART initiation, or even made worse by pressure that the expectation of SDI is perceived to place on patients [9,10]. Overall attrition at 8 months was lower in the intervention arm in both trials [5,6], but its timing differed.…”
Section: Introductionmentioning
confidence: 99%
“…While evidence from the SLATE trials [ 5 , 6 ] and others [ 7 , 8 ] demonstrates improved uptake of ART with SDI compared to standard care, concerns remain whether the benefits of SDI can be translated into improved retention once on treatment, or if instead attrition is simply shifted from before to soon after ART initiation, or even made worse by pressure that the expectation of SDI is perceived to place on patients [ 9 , 10 ]. Overall attrition at 8 months was lower in the intervention arm in both trials [ 5 , 6 ], but its timing differed.…”
Section: Introductionmentioning
confidence: 99%